Fungi: outstanding source of novel chemical scaffolds. Issue 2 (1st February 2020) - Liu, Zhen; Zhao, Jing-Yi; Sun, Sen-Feng; Li, Yong; Liu, Yun-Bao
Abstract: A large number of remarkable studies on the secondary metabolites of fungi have been conducted in recent years. This review gives an overview of one hundred and sixty-seven molecules with novel skeletons and their bioactivities that have been reported in seventy-nine articles published from 2013 to 2017. Our statistical data showed that endophytic fungi and marine-derived fungi are the major sources of novel bioactive secondary metabolites. Abstract :